Advanced Controllers Implementation for Speed Control Analysis of Two Mass Drive System - et.al, D.Devasena (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The speed control of two mass drive systems is presented in this paper. For the purpose of analysis, PI, Linear Matrix Inequality controller and Internal Model Controller are chosen. Tuning of PI controller is achieved by Zeigler Nichols method, whereas the LMI and IMC are adapted with the conventional method of tuning. The various simulations are carried out in order to analyze the performance index of these controllers and to fix the best controller, and the results are compared